Determinants of Binge Eating Behaviours in Adolescents - Febriani, Nurasifah; Handayani, Oktia Woro Kasmini (Universitas Aisyah Pringsewu, 2023)
Binge eating behavior is described as a loss of control over eating large amounts of food compared to ordinary people over a period of time. Binge eating is common among adolescents and poses significant health risks. In Indonesia, research on this issue is limited. This study explores how self-esteem, dietary habits, BMI, and emotional control relate to binge eating. This research uses a quantitative method with a cross-sectional study. The sample in the study amounted to 346 participants. Data collection techniques using the Modified BES (Binge Eating Scale), DERS-SF (Difficulty Emotional Regulation - Short Form), RSES (Rosenberg Self Esteem Scale), and dietary restraint questionnaire that the researcher made himself. The participants with binge eating behavior were 118 (33.5%). A significant relationship exists between binge eating and self-esteem, emotion regulation, and dietary restraint, but not with BMI. Dietary restraint has the most vital relationship. This study concludes that binge eating behavior has a high prevalence among adolescents. Emotion regulation, self-esteem, and dietary restraint were proven as risk factors in this study, and the most significant factor was dietary restraint. BMI Z-score showed a negative correlation with the incidence of binge eating in adolescents. Suggestion: Schools are expected to provide emotional assistance through counseling guidance to students related to mental health and knowledge about eating behavior and proper diet.